Recycling method of positive electrode material

Through a green, fast and efficient cathode material recycling method, including impurity removal, heat treatment and lithium replenishment steps, the problems of high energy consumption, high cost and serious environmental pollution in cathode material recycling in the existing technology have been solved, and NCM materials have been realized. Efficient recycling and reuse.

CN119361885APending Publication Date: 2025-01-24JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411526204.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing cathode material recycling methods have problems such as high energy consumption, high cost and serious environmental pollution. Especially when dealing with NCM materials, complex steps and large amounts of chemicals are required, resulting in dual economic and environmental challenges.

Method used

A green, fast, and efficient cathode material recycling method is adopted, which includes collecting the cathode plates of spent lithium-ion batteries, heat-treating them after removing impurities, and then mixing them with lithium replenishing agents and deep eutectic solvents. Through these steps, the cathode materials are restored. Electrochemical activity.

Benefits of technology

Effectively improve the electrochemical activity of waste positive poles, reduce energy consumption and cost, reduce environmental pollution, and realize the efficient recycling and reuse of NCM materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361885A_ABST
    Figure CN119361885A_ABST
Patent Text Reader

Abstract

The invention discloses a recovery method of a positive electrode material, and belongs to the technical field of battery material preparation. The invention provides a green and rapid recovery method: the Al impurity is used as a controllable dopant to recover the degraded NCM material, in the direct recovery process, the Al impurity left in the positive electrode material in the disassembly process is used for repairing element vacancies in NCM crystal lattices, and the electrochemical performance of the recovered material is improved. In addition, the compensation of Al on the loss of Ni, Co and Mn elements in the NCM structure is expected to be beneficial to improving the stability of the layered structure in the normal recovery process. The method further comprises a lithium supplement reaction step for element supplement, and lithium-containing DES is adopted to repair the completely degraded NCM so as to recover the structure of the NCM material. The method is good in sustainability, the lithium-containing DES can be recycled, and no harmful waste is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recovering positive electrode materials, belonging to the technical field of batteries. Background Art

[0002] The disposal of scrapped electric and hybrid electric vehicle ternary power batteries has gradually become an environmental challenge and social issue. Proper treatment of waste batteries, especially the effective recycling of NCM materials (nickel-cobalt-manganese ternary materials), can not only save limited reserves of precious metals (such as Li, Ni, Co, and Mn), but also protect the earth's environment from secondary pollution by toxic chemicals.

[0003] However, the current direct regeneration strategies for cathode materials can be roughly divided into two types: pyrometallurgy and hydrometallurgy. Generally speaking, pyrometallurgy requires high-temperature reduction roasting to decompose the stable waste cathode materials into mixed alloys for further extraction, which consumes a lot of energy. In the hydrometallurgical process, acid leaching is used instead of the high-temperature reduction step for decomposition, and then the metal elements are extracted at a lower temperature by precipitation, ion exchange or electrodeposition. However, due to the high liquid-to-solid ratio during the leaching process, a large amount of wastewater that requires further treatment is generated. The large-scale use of acids, reducing agents, precipitants and other reagents also increases the cost of the entire process. Therefore, the existing pyrometallurgical and hydrometallurgical processes have major problems in terms of economic feasibility and environmental friendliness.

[0004] The main mechanism of NCM material degradation is: element loss. Long-term cycling of the battery will lead to significant loss of lithium in NCM; on the other hand, transition metal (TM) elements slowly dissolve into the electrolyte, causing internal structure collapse. During the disassembly of the battery, the solvent-free disassembly scheme widely used in the industry inevitably leads to the mixing of aluminum impurities in the spent NCM positive electrode material. In this case, a lot of operations and a lot of chemicals are required to remove aluminum impurities to reduce their adverse effects on recycled materials.

[0005] Therefore, restoring the composition and structure of recycled NCM materials to the same state as fresh batteries must include impurity removal, element compensation (including lithium and TMs), and structural repair (including atomic and micro / nano defects). This method has complex steps and high costs. Summary of the invention

[0006] To solve the above problems, the present invention provides a green, fast and efficient positive electrode recycling method, which can effectively improve the electrochemical activity of waste positive electrodes.

[0007] An object of the present invention is to provide a method for recycling positive electrode materials of lithium batteries, comprising the following steps:

[0008] S1. Collecting the positive electrode sheets of the waste lithium-ion batteries, removing impurities, and obtaining a precursor after the impurities are removed; the precursor is composed of the positive electrode active material and the metal particles in the current collector;

[0009] S2, heat-treating the precursor at a set temperature in an oxygen-containing condition to obtain a heat-treated product;

[0010] S3, mixing the heat-treated product with a lithium supplement agent and a deep eutectic solvent, and collecting a solid portion to obtain a recovered product;

[0011] The current collector is an aluminum current collector, the material of the metal particles is aluminum, and the positive electrode active material includes a nickel-cobalt-manganese ternary material.

[0012] Furthermore, the impurity removal comprises the following steps:

[0013] S01, separating the active layer and the current collector of the positive electrode plate to obtain a mixture containing the active layer material and the metal in the current collector, crushing the mixture, and washing and drying after the crushing;

[0014] S02, treating the dried product in step S01 with an impurity remover, collecting and drying the solid portion after the treatment, to obtain the precursor.

[0015] Furthermore, in the impurity removal process, the impurity remover used is an organic solvent, especially an organic solvent that can dissolve impurities such as binders in the positive electrode material, and most preferably environmentally friendly and biodegradable N-methyl-2-pyrrolidone (NMP).

[0016] Furthermore, in step S01, drying is performed at 40-80°C.

[0017] Furthermore, in step S02, drying is performed at 60-100°C.

[0018] Further, in step S02, the solid-to-liquid ratio of the dried product to N-methyl-2-pyrrolidone is 0.12-0.3 g / mL, for example, 0.12 g / mL, 0.13 g / mL, 0.14 g / mL, 0.15 g / mL, 0.16 g / mL, 0.17 g / mL, 0.18 g / mL, 0.19 g / mL, 0.20 g / mL, 0.21 g / mL, 0.22 g / mL, 0.23 g / mL, 0.24 g / mL, 0.25 g / mL, 0.26 g / mL, 0.27 g / mL, 0.28 g / mL, 0.29 g / mL, 0.30 g / mL, etc., including but not limited to the ratios listed above.

[0019] Further, in step S02, the temperature of the treatment with N-methyl-2-pyrrolidone is 60°C-120°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, etc., including but not limited to the temperatures listed above.

[0020] Furthermore, in step S2, the mass percentage of metallic aluminum in the product after the heat treatment is also the same.

[0021] Further, in step S2, the set temperature is not less than 200°C; preferably, the set temperature is 200-600°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, etc., including but not limited to the temperatures listed above.

[0022] Furthermore, in step S2, the heat treatment time is 3-6 hours, such as 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, etc., including but not limited to the times listed above.

[0023] Furthermore, in step S2, after the heat treatment, the heat-treated product is also cooled, washed and dried, preferably at 40-80°C.

[0024] Furthermore, in step S3, the lithium supplement may be a lithium-containing compound that is compatible with the deep eutectic solvent system, and most preferably is lithium polyol.

[0025] Further, in step S3, the molar ratio of the lithium supplement agent to the deep eutectic solvent is (2-2.8): (1.3-2), for example, 2:1.3, 2:1.5, 2:1.8, 2:1.9, 2:2, 2.1:1.6, 2.3:1.6, 2.6:1.6, 2.7:1.6, 2.1:1.3, 2.2:1.5, 2.5:1.8, 2.7:1.9, etc., including but not limited to the ratios listed above.

[0026] Further, in step S3, the volume ratio of the mass of the heat-treated product to the mixed solution consisting of the lithium supplement agent and the deep eutectic solvent is 0.03-0.06 g / mL, for example, 0.03 g / mL, 0.036 g / mL, 0.04 g / mL, 0.045 g / mL, 0.05 g / mL, 0.055 g / mL, 0.06 g / mL, etc., including but not limited to the ratios listed above.

[0027] Further, in step S3, the mixing temperature during the deep eutectic solvent treatment is 60-100°C, for example, 60°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc., including but not limited to the temperatures listed above.

[0028] Further, in step S3, the mixing time during the deep eutectic solvent treatment is 5-15 hours, such as 5.5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, 9.7 hours, 10 hours, 10.2 hours, 10.5 hours, 11 hours, 12 hours, 13 hours, 14 hours, 14.5 hours, etc., including but not limited to the times listed above.

[0029] Furthermore, after step S3, the method further comprises washing and drying the recovered product; preferably, the drying is performed at 100-180°C.

[0030] Furthermore, in the nickel-cobalt-manganese ternary material, the molar ratio of Ni, Co and Mn is (8-9.5):(0.2-0.8):(0.2-0.8), and the sum of the molar ratios is 1.

[0031] The present invention also provides a positive electrode plate prepared using the above recycled materials, comprising a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer comprises the above recycled lithium battery positive electrode material, a conductive agent and a binder.

[0032] Furthermore, the positive electrode active layer comprises the following components in mass percentage: 75-95% of recycled positive electrode material, 5-15% of conductive agent and 5-15% of binder.

[0033] Furthermore, the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.

[0034] Further, the binder can be a binder well known to those skilled in the art without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF is selected.

[0035] The present invention also provides a lithium-ion battery comprising a negative electrode sheet, a separator and an electrolyte, and more importantly, the positive electrode sheet.

[0036] Beneficial effects of the present invention:

[0037] The present invention develops a green and efficient two-step recycling strategy to directly and effectively regenerate waste NCM cathode materials. In the first step of the reaction, the aluminum impurities remaining in the disassembly process are used as doping elements to supplement the small loss of transition metals in the waste NCM. The above-mentioned "aluminum impurities" are used to repair the element vacancies in the NCM lattice. A trace amount of Al doping stabilizes the layered structure and improves the cycle stability of the NCM cathode material. In the second step, a system consisting of a lithium replenisher and a deep eutectic solvent is used for lithium replenishment. DES, as a carrier, promotes the selective transport of lithium and TM elements, thereby directly repairing the degraded NCM, optimizing the regeneration / repair process, and ensuring the effective supply of lithium and TM elements in the degraded structure to restore its ideal electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Long cycle test results of batteries prepared with different positive electrode materials. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0040] As described in the background technology, in the recycling process of waste lithium-ion batteries, especially positive electrode materials NCM, the separation of positive electrode materials and foil is a major difficulty. The process involved is complicated, which increases the cost, and the existing view is generally that the presence of foil will have an adverse effect on the recycling process and the recycled materials. In order to overcome this problem, the present invention proposes a new method for separating excellent positive electrode materials (nickel-cobalt-manganese ternary materials) from waste lithium batteries without the need for precise separation of positive electrode materials and foil.

[0041] Specifically:

[0042] The present invention provides a method for recycling anode materials of lithium batteries, comprising the following steps:

[0043] S1. Collecting the positive electrode sheets of the waste lithium-ion batteries, removing impurities, and obtaining a precursor after the impurities are removed; the precursor is composed of the positive electrode active material and the metal particles in the current collector;

[0044] S2, heat-treating the precursor at a set temperature in an oxygen-containing condition to obtain a heat-treated product;

[0045] S3, mixing the heat-treated product with a lithium supplement agent and a deep eutectic solvent, and collecting a solid portion to obtain a recovered product;

[0046] The current collector is an aluminum current collector, the material of the metal particles is aluminum, and the positive electrode active material includes a nickel-cobalt-manganese ternary material.

[0047] In the present invention, the metal in the current collector is used to dope the recycled NCM material, eliminating the step of completely separating the current collector from the positive electrode active material in the traditional recycling process. The current collector is scraped and sampled and then mixed with the waste positive electrode active material. The required amount of current collector metal can be added as needed, and it has been verified that appropriate aluminum doping can improve the electrical properties of the recycled NCM material. Therefore, the present invention not only avoids the current insurmountable difficulties through clever design, but also can be said to have broken the "technical prejudice" that the current collector and the positive electrode active material must be completely separated to a certain extent, which is also one of the innovations of the present invention.

[0048] On the basis of the above, the present invention also optimizes and improves the recycling process, including but not limited to adjusting the parameters in the recycling process and specific process steps. Specifically:

[0049] In the present invention, the disassembled positive electrode sheet is firstly cleaned to remove the binder and conductive agent "impurities" therein, and the metal from the current collector remaining on the active material does not need to be cleaned. At this time, the system includes NCM and the current collector metal, which are crushed to obtain a mixture, and the mixture is heat-treated under set conditions, 4Al+3O2→2Al2O3 at high temperature, and Al2O3 is mixed into the NCM oxide during the sintering process to obtain a heat-treated product. Finally, the heat-treated product is supplemented with lithium under deep eutectic solvent conditions to obtain a repaired NCM material.

[0050] Preferably, the impurity removal comprises the following steps:

[0051] S01, separating the active layer and the current collector of the positive electrode plate to obtain a mixture containing the active layer material and the metal in the current collector, crushing the mixture, and washing and drying after the crushing;

[0052] S02, treating the dried product in step S01 with an impurity remover, collecting and drying the solid portion after the treatment, to obtain the precursor.

[0053] Preferably, in the impurity removal process, the impurity remover used is an organic solvent, especially an organic solvent that can dissolve impurities such as binders in the positive electrode material, and most preferably environmentally friendly and biodegradable N-methyl-2-pyrrolidone (NMP).

[0054] Preferably, since impurities such as conductive agents are insoluble in water, the impurity removal process further includes a step of removing impurities such as conductive agents in the positive electrode active layer by washing.

[0055] Among them, in step S01, there is no special requirement for the crushing, and the crushing state can be obtained by ball milling, air flow milling, etc., and there is no specific requirement for the degree of crushing.

[0056] About drying operation:

[0057] In step S01, drying is performed at 40-80°C;

[0058] In step S2, after the heat treatment, the heat-treated product is also cooled, washed and dried, preferably at 40-80° C.;

[0059] The above drying at a relatively low temperature, in addition to helping to remove the moisture from the electrode material after washing, can also avoid thermal degradation and structural changes of the material caused by high temperature, and help the material maintain its integrity and original physical and chemical properties, which is very important for subsequent material reuse and further processing.

[0060] In step S02, drying is performed at 60-100°C;

[0061] Within the temperature range of 60-100°C, the evaporation rate of N-methyl-2-pyrrolidone will accelerate and its physical properties (such as viscosity and solubility) will change, which will help to completely remove it from the battery material, thereby reducing its impact on the recycled materials, while avoiding thermal damage to the battery material and improving recycling efficiency.

[0062] After step S3, the method further comprises washing and drying the recovered product; preferably, drying the recovered product at 100-180° C.;

[0063] During the recycling process, according to the characteristics of the positive electrode material, appropriate temperature is required to remove the adsorbed moisture and solvent without affecting the crystal structure, surface characteristics and chemical stability of the material, so as to ensure the integrity and recycling efficiency of the material.

[0064] Preferably, the solid-to-liquid ratio of the dried product to N-methyl-2-pyrrolidone in step S02 is 0.12-0.3 g / mL. The solid-to-liquid ratio is an important operating parameter, which determines the degree of contact between the solvent and the impurities that need to be removed in the battery material. The appropriate solid-to-liquid ratio can ensure that NMP fully penetrates into the pores of the battery material and effectively dissolves and removes impurities. Different solid-to-liquid ratios may also affect the dissolution selectivity of NMP to specific impurities. The present invention not only optimizes the impurity removal process by adjusting the solid-to-liquid ratio, making the target impurities easier to remove, but also minimizes the loss of valuable materials, which also guarantees product quality to a certain extent. Moreover, too high a solid-to-liquid ratio may also lead to a waste of solvents, and too low a solid-to-liquid ratio cannot effectively remove impurities.

[0065] In the step S02, the solid-to-liquid ratio of the dried product to N-methyl-2-pyrrolidone may be 0.12 g / mL, 0.13 g / mL, 0.14 g / mL, 0.15 g / mL, 0.16 g / mL, 0.17 g / mL, 0.18 g / mL, 0.19 g / mL, 0.20 g / mL, 0.21 g / mL, 0.22 g / mL, 0.23 g / mL, 0.24 g / mL, 0.25 g / mL, 0.26 g / mL, 0.27 g / mL, 0.28 g / mL, 0.29 g / mL, 0.30 g / mL, etc., including but not limited to the ratios listed above.

[0066] Preferably, in step S02, the temperature of the treatment with N-methyl-2-pyrrolidone is 60° C.-120° C. At this temperature, the movement speed of NMP molecules is increased, and the migration of impurities in NMP can be promoted. The solubility of NMP for impurities is also improved accordingly, ensuring the separation efficiency. Although high temperature helps to improve the impurity removal efficiency, too high a temperature will cause thermal decomposition of the NCM material, affecting the quality of the recycled material.

[0067] In step S02, the temperature of N-methyl-2-pyrrolidone treatment is 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, etc., including but not limited to the temperatures listed above. The best treatment temperature in the present invention is 60°C.

[0068] In step S1, the mass percentage of metallic aluminum in the precursor is 1wt%-6wt%, and accordingly, the mass percentage of metallic aluminum in the product after heat treatment is also 1wt%-6wt%. After many attempts by the inventors, it was found that the structure and performance of the recycled material can be improved by first oxidizing aluminum during the doping process and then doping it into the NCM lattice. At the same time, the "aluminum impurities" remaining in the disassembly process are used as doping elements to supplement the small loss of transition metals in the waste NCM. The "aluminum impurities" can be used to repair the element vacancies in the NCM lattice. A trace amount of Al doping can stabilize the layered structure and improve the cycle stability of the NCM cathode material. It can also be seen from the experimental verification that compared with no doping, when Al is doped in an appropriate amount, the battery capacity and cycle performance are significantly improved, and the performance of the group with excessive doping is also reduced. This may be because excessive Al will accumulate on the surface of the grains to form dendrites, or uneven deposition will affect the interface stability, and these deposited metals cannot participate in the electrochemical reaction, while hindering the transmission of ions.

[0069] During the heat treatment process, the set temperature is not less than 200°C; preferably, the set temperature is 200-600°C. The selection of heat treatment temperature during the recycling process is very critical because it directly affects the structure and properties of the material. Specifically, the sintering temperature affects the crystal structure and microstructure of the positive electrode material, and the sintering temperature will lead to different micromorphologies, thereby affecting the electrochemical properties of the material. Moreover, the appropriate sintering temperature can increase the specific surface area and pore volume of the material, thereby increasing the discharge capacity and cycle stability, and increasing the reuse value of the recycled material.

[0070] Preferably, the heat treatment time is 3-6 hours. Heat treatment time is also a key process parameter in the battery positive electrode material recycling process. Appropriate sintering time can promote grain growth in the material, improve the density and structural compactness of the material, which helps to improve the conductivity and mechanical strength of the battery. Appropriate sintering time also helps to form a good crystal structure, increase the diffusion rate of ions, and improve the capacity, cycle stability and rate performance of the battery, thereby improving the overall performance of the battery. Too long sintering time may cause excessive oxidation or reduction of the material surface, affecting the chemical stability and electrochemical properties of the material. Excessive sintering time will also increase energy consumption and production costs, while too short a time may lead to insufficient sintering of the material, affecting the material performance.

[0071] In step S2, the heat treatment temperature is 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, etc., including but not limited to the temperatures listed above; the heat treatment time is 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, etc., including but not limited to the times listed above. In the present invention, the best heat treatment temperature is 400°C and the heat treatment time is 4h according to the electrical properties of the positive electrode material NCM recycled material.

[0072] In step S3, the lithium replenisher can be a lithium-containing compound that is compatible with the deep eutectic solvent system, and is most preferably lithium polyol. In the present invention, the deep eutectic solvent provides an environment for lithium replenishment, and a lithium replenisher that is soluble in the deep eutectic solvent is selected. This lithium replenishment process makes it possible to directly recycle degraded NCM. The lithium replenishment conditions are further optimized:

[0073] Preferably, the molar ratio of the lithium supplement agent to the deep eutectic solvent is (2-2.8): (1.3-2); the volume ratio of the mass of the product after the heat treatment to the mixed solution composed of the lithium supplement agent and the deep eutectic solvent is 0.03-0.06 g / mL. Preferably, during the deep eutectic solvent treatment, the temperature is 60-100°C and the time is 5-15 hours.

[0074] The lithium replenishment system has a significant impact on the initial efficiency of batteries prepared from recycled materials. The capacity loss of the positive electrode material mainly comes from the structural changes of the positive electrode material after the first discharge, which reduces the positions where lithium can be inserted in the material, making it impossible for lithium ions to return to their original positions, resulting in capacity loss. The lithium replenishment environment of the present invention improves this problem to a certain extent, and the battery performance is optimal at a specific ratio. The system of the present invention can increase the density of the electron pathway in the contact interface during the lithium replenishment process, reduce the collapse of the electron pathway and thus reduce the blockage of the electrochemical circuit, and reduce the irreversible capacity loss of the battery in the initial charge and discharge cycle, which helps to increase the actual cycle capacity of the battery and extend the service life of the battery.

[0075] In the step S3, the molar ratio of the lithium supplement agent to the deep eutectic solvent is 2:1.3, 2:1.5, 2:1.8, 2:1.9, 2:2, 2.1:1.6, 2.3:1.6, 2.6:1.6, 2.7:1.6, 2.1:1.3, 2.2:1.5, 2.5:1.8, 2.7:1.9, etc., including but not limited to the ratios listed above. In the present invention, the best ratio is 2.5:1.6 according to the electrical properties of the positive electrode material NCM recycled material.

[0076] In step S3, the mass ratio of the heat-treated product to the volume ratio of the mixed solution of the lithium supplement agent and the deep eutectic solvent is 0.03 g / mL, 0.036 g / mL, 0.04 g / mL, 0.045 g / mL, 0.05 g / mL, 0.055 g / mL, 0.06 g / mL, etc., including but not limited to the above-mentioned ratios. In the present invention, the best ratio is 0.03 g / mL according to the electrical properties of the positive electrode material NCM recycled material.

[0077] In the step S3, the mixing temperature during the deep eutectic solvent treatment process is 60°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc., including but not limited to the temperatures listed above. In the present invention, the optimal temperature selected according to the electrical properties of the positive electrode material NCM recycled material is 70°C.

[0078] In the step S3, the mixing time during the deep eutectic solvent treatment is 5.5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 9.5 hours, 9.7 hours, 10 hours, 10.2 hours, 10.5 hours, 11 hours, 12 hours, 13 hours, 14 hours, 14.5 hours, etc., including but not limited to the times listed above. In the present invention, the best time selected according to the electrical properties of the positive electrode material NCM recycled material is 10 hours.

[0079] In the nickel-cobalt-manganese ternary material of the present invention, the molar ratio of Ni, Co and Mn is (8-9.5):(0.2-0.8):(0.2-0.8), and the sum of the molar ratios is 1.

[0080] Preferably, the steps are as follows:

[0081] 1. The used lithium-ion battery was discharged in a 5%-20% NaCl solution for 45-60 hours, and then disassembled by physical methods in a fume hood. After the core was removed, the core was disassembled, and the cathode plate obtained was immediately rinsed with dimethyl carbonate 2-3 times to remove the residual electrolyte to obtain the cathode plate.

[0082] 2. Separate the cathode composite material (including NCM material, carbon black and PVDF binder) from the Al current collector (scrape out the powder) and crush it. The obtained powder therefore contains waste NCM, PVDF, Al particles and conductive impurities.

[0083] 3. The obtained powder was washed with water several times (to remove dimethyl carbonate and other water-soluble impurities) and dried overnight at 40-80°C. The dried powder was then leached with N-methyl-2-pyrrolidone (solid-to-liquid ratio of 0.12-0.3 g / mL) at 60-120°C for 2-6 h while stirring, filtered, and dried at 60-100°C for 10-30 h.

[0084] 4. The mixture of waste NCM and residual Al particles obtained in step (3) is transferred to a crucible and heat treated in a furnace at 200-600°C for 3-6h. After cooling, it is washed with deionized water 2-3 times to remove soluble Li salts (surface residual lithium of NCM), and dried at 40-80°C overnight to obtain Al-doped NCM powder (Al doping range: 1-6wt%).

[0085] 5. Betaine, lithium ethylene glycol and urea were mixed in a certain molar ratio and stirred at 30-50°C for 5-30 min to prepare a deep eutectic solvent (DES). Aluminum-containing NCM material was added to the deep eutectic solvent at a solid-liquid ratio of 0.03-0.06 g / mL and stirred at 60-100°C for 10 h.

[0086] 6. The formed slurry was filtered, washed with deionized water (to remove the deep eutectic agent residue), and dried at 100-180°C for 6-8h to obtain the recycled material Li[Ni0.90CoxMnyAl(0.1-xy)]O2, 0<X<0.05, 0<Y<0.05.

[0087] The present invention also provides a positive electrode plate prepared using the above recycled materials, comprising a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, wherein the positive electrode active layer comprises the above recycled lithium battery positive electrode material, a conductive agent and a binder.

[0088] Preferably, the positive electrode active layer comprises the following components in mass percentage: 75-95% of recycled positive electrode material, 5-15% of conductive agent and 5-15% of binder.

[0089] Preferably, the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.

[0090] Preferably, the binder is a binder well known to those skilled in the art, without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF is selected.

[0091] Preferably, the thickness of the positive electrode active layer is in the range of 100-300 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, etc., including but not limited to the thickness values ​​listed above.

[0092] The embodiment of the present invention also provides a method for preparing the positive electrode sheet as described above, comprising the following steps:

[0093] S01, preparing a positive electrode active slurry by using a formulated amount of positive electrode material, a conductive agent and a binder;

[0094] S02, coating the positive electrode active slurry on at least one side of the current collector along the thickness direction, obtaining a positive electrode active layer after drying, and pressing to obtain the positive electrode plate.

[0095] Preferably, the current collector is aluminum foil, or other materials that can be used as a current collector; preferably, the thickness of the current collector is in the range of 5-14 μm.

[0096] The embodiments of the present invention also provide a lithium-ion battery comprising a negative electrode plate, a separator and an electrolyte, and more importantly, the positive electrode plate.

[0097] Preferably, the negative electrode plate comprises a negative electrode active layer; the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder.

[0098] Preferably, the negative electrode active layer comprises the following components in mass percentage: 75-95% of negative electrode active material, 5-15% of conductive agent and 5-15% of binder.

[0099] Preferably, the negative electrode active material is selected from one or more of artificial graphite, natural graphite, silicon, silicon oxide, titanium phosphorus oxide (including sodium titanium phosphate, sodium titanium manganese phosphate, titanium phosphate).

[0100] Preferably, the conductive agent is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.

[0101] Preferably, the binder is a negative electrode binder well known to those skilled in the art without any particular limitation, such as one or more of chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer.

[0102] Preferably, the type of the diaphragm is any diaphragm well known to those skilled in the art without any particular limitation, such as one or more of polyethylene, polypropylene, polyacrylonitrile, polyacrylonitrile fiber, polyamic acid, polyimide, polyamide, polydopamine, polyarylethersulfone, polyvinylidene fluoride, polyethylene oxide, polyethylene terephthalate, polyester, non-woven fabric membrane and cellulose paper-based isolation membrane.

[0103] Preferably, the electrolyte is an electrolyte well known to those skilled in the art without any special restrictions, the solvent is at least one of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether; the electrolyte salt is at least one of sodium perchlorate, sodium bis(oxalate)borate, and sodium hexafluorophosphate.

[0104] Example 1

[0105] A method for recycling waste lithium-ion battery positive electrode material LiNi0.9Co0.05Mn0.05O2 (NCM9055), comprising the following steps:

[0106] (1) The used lithium-ion battery was discharged in a 15% NaCl solution for 50 hours and then disassembled by a physical method in a fume hood. After the winding core was removed, the winding core was disassembled and the positive electrode sheet was immediately rinsed with dimethyl carbonate for 3 times to remove the residual electrolyte, thereby obtaining a positive electrode sheet.

[0107] (2) The positive electrode composite material (including NCM material, carbon black and PVDF binder) is separated from the Al current collector (scraping to remove powder) and crushed. The obtained powder therefore contains waste NCM, PVDF, Al particles and conductive impurities.

[0108] (3) The obtained powder was washed with water several times and dried overnight at 60° C. The dried powder was then leached with N-methyl-2-pyrrolidone (solid-to-liquid ratio of 0.2 g / mL) at 60° C. for 5 h while stirring, filtered, and dried at 70° C. for 24 h.

[0109] (4) After the drying process, the Al-containing NCM powder was fully blended and uniformly mixed, and an ICP test was performed to detect the blending level of Al particles in the material, and the blending level was controlled at 1 wt %.

[0110] (5) The resulting mixture of spent NCM and residual Al particles was transferred to a crucible and heat treated in a furnace at 400°C for 4 h. After the collected samples were cooled, they were washed twice with deionized water to remove soluble Li salts and dried at 40°C overnight to obtain Al-containing NCM powder.

[0111] (6) Betaine, lithium ethylene glycol, and urea were mixed in a molar ratio of 1.4:2.5:0.2 and stirred at 35°C for 10 min to prepare a deep eutectic solvent (called DES). Aluminum-containing NCM material was added to the deep eutectic solvent at a solid-liquid ratio of 0.03 g / mL and stirred at 70°C for 10 h.

[0112] (7) The formed slurry was filtered, washed with deionized water, and dried at 120° C. for 8 h to obtain a regenerated material.

[0113] Example 2

[0114] In step (4), the mixing level of Al particles in the material is controlled to be 2 wt %, and the other steps are carried out according to Example 1.

[0115] Example 3

[0116] In step (4), the mixing level of Al particles in the material is controlled to be 3 wt %. The other steps are carried out according to Example 1.

[0117] Example 4

[0118] In step (4), the mixing level of Al particles in the material is controlled to be 6 wt %. The other steps are carried out according to Example 1.

[0119] Example 5

[0120] In step (5), heat treatment is performed in a furnace at 200° C. for 4 h, and the other steps are performed according to Example 3.

[0121] Example 6

[0122] In step (5), heat treatment is performed in a furnace at 600° C. for 4 h, and the other steps are performed according to Example 3.

[0123] Example 7

[0124] In step (5), heat treatment is performed in a furnace at 400° C. for 3 h, and the other steps are performed according to Example 3.

[0125] Example 8

[0126] In step (5), heat treatment is performed in a furnace at 400° C. for 6 h, and the other steps are performed according to Example 3.

[0127] Example 9

[0128] In step (6), the aluminum-containing NCM material is added to the deep eutectic solvent at a solid-liquid ratio of 0.06 g / mL and stirred at 70° C. for 10 h. The other steps are performed according to Example 3.

[0129] Example 10

[0130] In step (6), betaine, lithium ethylene glycol and urea were mixed in a molar ratio of 1.2:2.0:0.5 and stirred at 35° C. for 10 min to prepare a deep eutectic solvent (referred to as DES). The other steps were performed according to Example 3.

[0131] Embodiment 11

[0132] The DES system in step (6) was replaced by NMP, and the other steps were carried out according to Example 3.

[0133] Comparative Example 1

[0134] Use fresh cathode powder from the same batch as the waste NCM material.

[0135] Comparative Example 2

[0136] In step (4), the mixing level of Al particles in the material is controlled to be 0 wt %, and the other steps are carried out according to Example 3.

[0137] The following additional treatment is required to control the mixing level of Al particles to 0: the aluminum foil is dissolved by alkaline leaching. Specifically, the powder is passed through a NaOH solution once. Since aluminum is an amphoteric metal, it can be dissolved in acid and alkaline solutions, while the metals in the electrode material cannot react with alkali.

[0138] Comparative Example 3

[0139] In step (4), the mixing level of Al particles in the material is controlled to be 10 wt %. The other steps are carried out according to Example 3.

[0140] Test Case

[0141] The positive electrode materials prepared in all embodiments and test examples were prepared into batteries, and the performance of the prepared batteries was tested. The following steps were included:

[0142] Assembly of the battery: The positive electrode is prepared with a slurry of 90wt% of the prepared recycled material, 6wt% of polyvinylidene fluoride (PVDF) binder and 4wt% of acetylene black. The obtained slurry is coated on aluminum cloth. After drying and rolling, the obtained positive electrode sheet is punched to obtain a disc with a diameter of 1.2cm. The items required for the experiment are placed in an oven at 60℃ for 12h of drying. Subsequently, a CR2032 button battery is assembled in an argon-protected glove box, in which the negative electrode is a purchased metal lithium sheet and the electrolyte is a mixed solution of 1mol / L LiPF6 dissolved in ethylene carbonate (EC) / dimethyl carbonate (DEC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1). The battery assembly order is negative electrode shell-metal lithium-diaphragm-positive electrode sheet-gasket-spring-positive electrode shell. A battery-withdrawal test was conducted under the following conditions: LR 2032, 0.1C, 2.5-4.3V, vs. Li+ / Li. The charging and discharging equipment used was a Blue Power charging and discharging instrument.

[0143] The test method of 1C gram capacity includes: at 25℃, let the battery stand for 30 minutes, charge to 4.25V at a constant current of 0.5C, then charge at a constant voltage until the current is less than 0.05C, let it stand for 15 minutes, discharge to 2.8V at a constant current of 1C, record the first cycle charge and discharge capacity, and calculate the gram capacity based on the weight of the positive electrode sheet, gram capacity = discharge capacity / mass of positive electrode active material.

[0144] The first coulombic efficiency test method includes: in the 1C gram capacity test, the first charging capacity and the discharge capacity are recorded simultaneously, and the first coulombic efficiency = discharge capacity / charge capacity.

[0145] Long cycle test: Place the prepared button battery in a high and low temperature cycler to set the temperature to test the high and low temperature performance of the battery. Set the temperature to 25°C, charge the lithium-ion battery to 4.25V at a 1C rate, then charge it at a constant voltage until the current is less than 0.05C, and then discharge it to 2.8V at a 1C rate. Perform a cycle test in this full charge and discharge form until the discharge capacity of the lithium-ion battery decays to 80% of the initial capacity, and record the number of cycles at this time.

[0146] The gram capacity and first effect test results are as follows:

[0147] Table 1 Gram capacity and first effect (4.25V)

[0148]

[0149]

[0150] As can be seen from the table above, the first efficiency and gram capacity of different groups of batteries change with the changes in Al addition, sintering temperature, and time. Among them, the battery performance is best in the group with 3wt% Al addition, sintering temperature of 400℃, and heat treatment time of 4h, and the first efficiency performance even exceeds that of batteries made from newly prepared positive electrode materials. In addition, the deep eutectic solvent system also has a certain effect on the performance of the recycled positive electrode material, but in the battery performance test, it was found that its gram capacity and first efficiency can be kept comparable to those of the newly prepared positive electrode material.

[0151] The long cycle test results are shown in Figure 1 , where the blue line represents the battery prepared from the recycled material of Example 3, the yellow line represents the battery prepared from the fresh positive electrode material of Comparative Example 1, and the red line represents the battery prepared from the recycled material of Comparative Example 2. It can be seen from the figure that, compared with the recycled material without aluminum doping, the recycled material doped with aluminum of the present invention exhibits a very obvious excellent cycle performance. The recycled material prepared in Example 3 exhibits better performance than the newly prepared battery in the long cycle. Moreover, in the long-term cycle process, except for the initial capacity decay, the decay in the later cycle has a tendency to slow down, and can still maintain nearly 95% of the capacity after 1000 cycles.

[0152] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for recovering positive electrode materials, characterized in that: The following steps are involved: S1. Collecting the positive electrode sheets of the waste lithium-ion batteries, removing impurities, and obtaining a precursor after the impurities are removed; the precursor is composed of the positive electrode active material and the metal particles in the current collector; S2, heat-treating the precursor at a set temperature in an oxygen-containing condition to obtain a heat-treated product; S3, mixing the heat-treated product with a lithium supplement agent and a deep eutectic solvent, and collecting a solid portion to obtain a recovered product; The current collector is an aluminum current collector, the material of the metal particles is aluminum, and the positive electrode active material includes a nickel-cobalt-manganese ternary material.

2. The recycling method according to claim 1, characterized in that: In step S2, the mass percentage of metallic aluminum in the product after the heat treatment is 1wt%-6wt%.

3. The recycling method according to claim 1, characterized in that: In step S1, the impurity removal includes the following steps: S01, separating the active layer and the current collector of the positive electrode plate to obtain a mixture containing the active layer material and the metal in the current collector, crushing the mixture, and washing and drying after the crushing; S02, treating the dried product in step S01 with an impurity remover, collecting and drying the solid portion after the treatment, to obtain the precursor; Preferably, the impurity remover is an organic solvent containing N-methyl-2-pyrrolidone.

4. The recycling method according to claim 3, characterized in that: Contains at least one of the following characteristics: (1) In step S01, drying is performed at 40-80° C.; (2) In step S02, drying is performed at 60-100° C.; (3) In step S02, the mass ratio of the dried product in step S01 to the volume ratio of the impurity remover is 0.12-0.3 g / mL; (4) In step S02, the temperature of the impurity remover treatment is 60°C-120°C.

5. The recycling method according to claim 1, characterized in that: In step S2, at least one of the following features is included: (1) The set temperature is not less than 200°C; preferably, the set temperature is 200-600°C; (2) The heat treatment time is 3-6 hours.

6. The recycling method according to claim 1, characterized in that: In step S3, at least one of the following features is included: (1) The lithium supplement contains lithium polyol; (2) The molar ratio of the lithium supplement agent to the deep eutectic solvent is (2-2.8): (1.3-2); (3) The mass ratio of the heat-treated product to the volume ratio of the mixed solution consisting of the lithium supplement agent and the deep eutectic solvent is 0.03-0.06 g / mL; (4) The mixing temperature is 60-100° C.; (5) The mixing time is 5-15 hours.

7. The recycling method according to claim 1, characterized in that: The deep eutectic solvent consists of a hydrogen bond acceptor and a hydrogen bond donor, and preferably comprises at least one of the following features: (1) The hydrogen bond acceptor comprises betaine; (2) The hydrogen bond donor comprises urea; (3) In the deep eutectic solvent, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is (1.2-1.6): (0.1-0.4).

8. The recycling method according to claim 1, characterized in that: In the nickel-cobalt-manganese ternary material, the molar ratio of Ni, Co and Mn is (8-9.5):(0.2-0.8):(0.2-0.8).

9. The recycling method according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) Before step S3, the step of washing and drying the heat-treated product is also included; preferably, the drying is performed at 40-80° C.; (2) After step S3, the method further comprises washing and drying the recovered product; preferably, the drying is performed at 100-180°C.

10. A lithium ion battery, characterized in that: The lithium-ion battery contains the lithium battery positive electrode material obtained by the recovery method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Deep eutectic lithium supplement agent and method for repairing and regenerating positive electrode material of waste lithium ion battery by deep eutectic lithium supplement agent

    CN116130818A

  • Method for preparing electrocatalyst by efficiently recovering nickel, cobalt and manganese from waste lithium battery

    CN116315230A

  • Method for directly recycling positive electrode material of waste lithium (sodium) ion battery

    CN117352890A

  • Repair method of waste lithium iron phosphate battery positive electrode material and lithium ion battery

    CN118040128A